1999
DOI: 10.1097/00004647-199903000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption of Cerebral Cortex Fails to Increase during Continued Vibrotactile Stimulation

Abstract: The coupling of oxidative metabolism to the blood flow of the sensory motor hand area is uncertain. The authors tested the hypothesis that continued vibrotactile stimulation ultimately must lead to increased oxygen consumption consumption. Twenty-two healthy right-handed young volunteers underwent positron emission tomography (PET) with the [(15)O]water bolus injection method to measure water clearance (K1H2O an index of blood flow (CBF), and with the [(15)O]oxygen bolus inhalation method to measure CMR(O2). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
0
49
1
Order By: Relevance
“…However, the generated functional images suffer from statistical noise, which is attributed to the need for determination of multiple Rapid quantitative measurement of CMRO 2 and CBF N Kudomi et al parameters from a small amount of time-varying data. Cerebral blood flow images, in particular, suffer significantly from noise; precise determination of CBF often requires another PET scan with H 2 15 O injection (Meyer et al, 1987;Ohta et al, 1999;Fujita et al, 1999;Mintun et al, 2002). In contrast, the present approach can generate images of reasonable quality from a single 6-min PET scan.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the generated functional images suffer from statistical noise, which is attributed to the need for determination of multiple Rapid quantitative measurement of CMRO 2 and CBF N Kudomi et al parameters from a small amount of time-varying data. Cerebral blood flow images, in particular, suffer significantly from noise; precise determination of CBF often requires another PET scan with H 2 15 O injection (Meyer et al, 1987;Ohta et al, 1999;Fujita et al, 1999;Mintun et al, 2002). In contrast, the present approach can generate images of reasonable quality from a single 6-min PET scan.…”
Section: Discussionmentioning
confidence: 93%
“…The quality of the image suffers, however, from statistical noise because of the lack of predictability of the multiple parameters of CBF, CMRO 2 , and the arterial vascular compartment (V 0 ) and the limited acquisition time (Meyer et al, 1987;Ohta et al, 1992). Therefore, this technique has not been generally applied in clinical settings, but has been used primarily for research purposes (Fujita et al, 1999;Vafaee and Gjedde, 2000;Okazawa et al, 2001a, b;Mintun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, two positron emission tomography (PET) studies conducted by Fox et al (4,5) revealed that in humans large, stimulus-induced increases in CBF (Ϸ30% and 50%) were accompanied by only small increases in CMRO 2 (Ϸ5%). Others using PET and functional MRI confirmed these findings (6)(7)(8)(9)(10). The data indicated that, during short-term functional activation, CBF and CMRO 2 are not directly coupled.…”
mentioning
confidence: 78%
“…However, many studies have reported different results concerning the transient mismatch of ΔCMR Glc , CBF and ΔCMR O2 during functional activity (reviewed in Buxton (2010)). The characterization of these changes has been reported in positron emission tomography (PET) (Fox and Raichle, 1986;Fox et al, 1988;Fujita et al, 1999;Marrett and Gjedde, 1997;Vafaee and Gjedde, 2000) and in MR studies (Chen et al, 1993Davis et al, 1998;Hoge et al, 1999;Kim and Ugurbil, 1997;Kim et al, 1999;Lin et al, 2010;Liu et al, 2004;Vafaee et al, 2012;Wey et al, 2011), and their differences have been attributed to different experimental conditions and the brain region examined (Buxton, 2010;Rothman et al, 2003;Gjedde, 2000, 2004;Zhu et al, 2009). Nevertheless, an energy balance calculation suggests that the energy demands during visual activation are largely met through oxidative metabolism at all times (Mangia et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%